Strategi Guru Dalam Internalisasi Nilai Pancasila Melalui Pembiasaan : Studi Literatur dan Persepsi - Erika Duwi Septianingtias; Shofi Nur Amalia (Advances In Education Journal, 2026)
In the digital era, moral dedigration is a serious challenge for elementary school students, so internalizing Pancasila values from an early age is crucial for the exsistence of student character in elementary schools. This study aims so analyze teacher strategis in internalizing Pancasila values through habibutation metods and map educator’s practical preceptions in responding to contemporary moral challenges. The study show that medeling strategies are the most important determaint instrument in transforming abstract values into concrete actions. This researcher used a literature study and a perceptions survey of elementaryschool educators. The result found that modeling strategies are the most affective method. Implementation adjustments were made by integrating Pancasila values into independent curriculum ecosystem (p5) and active collaborating with parents. It can be concluded that the success of internalizing values is highly dependent on the consistency between educators’role models and the strengthening of the student environmental ecosystem holistically.